Integrative transformation of Candida albicans, using a cloned Candida ADE2 gene. - Kurtz, M B (1986)
Candida albicans is a diploid dimorphic yeast with no known sexual cycle. The development of a DNA transformation system would greatly improve the prospects for genetic analyses of this yeast. Plasmids were isolated from a Candida Sau3A partial library which complements the ade2-1 and ade2-5 mutations in Saccharomyces cerevisiae. These plasmids contain a common region, part of which, when subcloned, produces ade2 complementation. Among the small number of auxotrophs previously isolated in C. albicans, red adenine-requiring mutants had been identified by several groups. In two of these strains, the cloned Candida DNA transformed the mutants to ADE+ at frequencies of 0.5 to 5 transformants per micrograms of DNA. In about 50% of the transformants, plasmid DNA sequences became stably integrated into the host genome and, in the several cases analyzed by Southern hybridization, the DNA was integrated at the site of the ADE2 gene in one of the chromosomal homologs.